β-lactamase genes in carbapenem resistance Acinetobacter baumannii isolates from a Turkish university hospital - Umut Safiye Say Coskun; Emel Caliskan; Asegul Copur Cicek; Halbay Turumtay; Cemal Sandalli (Journal of Infection in Developing Countries)
Introduction: The spread of Acinetobacter baumannii, resistant to most of the available antimicrobial agents, is a serious health problem. The high rate of carbapenem resistance among Acinetobacter baumannii isolates is considered as a threat to public health. In this study, we aimed to determine the antibiotic resistance and related genes in carbapenem-resistant Acinetobacter baumannii isolates.